(untitled) (Kronika Bydgoska, 2020)
The social and cultural rebellion that developed throughout the Western world during the 1960s and 1970s was the first generational rebellion that led to elimination of many past phenomena, introducing their own ones (perhaps forever?). For obvious reasons, these phenomena looked different in the West and Poland. Bydgoszcz and its surrounding area had a relatively small impact on this cultural revolution. There was the lack of generational foundations and a big university. Bydgoszcz youth was a consumer of changes rather than their creator. Changes w ere also not facilitated by the media, both central and regional, which were not able to adjust the phenomenon of counterculture to the binding ideology.